'Five things i would like a community specialist palliative care service to provide' – a novel approach. Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - Traue, Dee
Abstract : Background: Isabel Hospice provides care for a population of 350, 000 across eastern Hertfordshire. Changes in our population and an increasing focus on choice in place of care have resulted in a growing demand for services to support patients to live and die at home. To inform future community service development, the hospice organised a series of focus groups for patients, carers and professionals. However, it was recognised that this method of engagement would only reach a limited number of stakeholders. Aim: To identify the priorities for community specialist palliative care service development of both stakeholders from local health and social care organisations and hospice staff. Methods: A postcard was developed asking the respondent to list 'five things I would like a community specialist palliative care service to provide'. The postcards also captured basic demographic data about the respondent. Over 300 postcards were distributed, with a covering letter, to local stakeholders including primary care teams, acute and mental health trust staff, adult care services and local voluntary sector organisations. Electronic versions of the postcard were distributed to all hospice staff and volunteers. Results: External respondents – 43 cards were returned, including 17 from district nurses and 14 from GPs. These included a total of 171 suggestions for what respondents would like the hospice to provide. The most popular themes were provision of 'hands on' care and access to advice and support 24/7. Internal respondents – 52 cards were returned, 17 from clinical staff and 31 from volunteers. These included a total of 157 suggestions, with the majority focusing on the development of day hospice and outpatient services. Conclusion: By adopting the novel approach of distributing the 'five things' postcard, the hospice was able to gather much wider stakeholder feedback than would have been possible by the use of focus groups alone.